Determinants of Approval Claims at Hospital Among COVID-19 Patients - Peter Herey; Nauri Anggita Temesvari (Faculty of Public Health, Hasanuddin University, Makassar, 2022)
The COVID-19 pandemic is an issue that is being faced by Indonesia and even most countries in the world. The impact due to the COVID-19 pandemic is disruption of hospital with cash flow. It was caused by the delay in hospital payment of claims which are not approved by Badan Penyelenggara Jaminan Sosial (BPJS Kesehatan). Siloam Sentosa Hospital Bekasi provides services for COVID-19 patients. However, out 81 claims of COVID-19 patients in August-October 2020, there were 65 claims (80.25%) not approved by BPJS Kesehatan. The purpose of this study was to analyze the factors that affect the approval claims among patients with COVID-19 at Siloam Sentosa Hospital Bekasi. This type of research was descriptive analysis with a quantitative approach. The research population was 108 claims and the sample used the total population. A Logistic regression test was used to analyze the data. The results of the study explained the completeness of claims, the quality of the medical resume, the completeness of filling out the epidemiological investigation form, and the quality of clinical coding that affected the approval claims. The study showed 21.5% of other factors that are not examined can affect the approval claims. Socialization of policies related to payment of claims to hospitals as well as monitor and evaluate from both hospitals and BPJS Kesehatan need to be improved to prevent claims that are not approved.